Auswirkungen von weniger Studierenden - Alexander Dilger (Universität Münster, Institut für Organisationsökonomik, 2024)
Die Zahl der Studierenden hat in Deutschland ihren Höhepunkt überschritten und dürfte zukünftig weiter abnehmen wie schon länger die Jahrgangsstärke und inzwischen auch die Studierneigung. Für die Hochschulen verschärft das den Wettbewerb und sie müssen sich vermehrt um ihre aktuellen und zukünftigen Studierenden bemühen. Die Studierenden profitieren davon, doch politisch schwindet ihr Einfluss und drohen Kürzungen der staatlichen Mittel für Hochschulen, die deshalb effizienter eingesetzt werden sollten. – – The number of students in Germany has passed its peak and is likely to continue to fall in the future, as has been the case for some time with the number of students per year and now also with the willingness to study. This means that competition is increasing for universities and they have to make more efforts to attract their current and future students. The students benefit from this, but politically their influence is waning and there is a threat of cuts in state funding for universities, which should therefore be used more efficiently.
Keywords: I23; I28; J11; 650; Demographie; Hochschule; Student; Studienfach; Wettbewerb